2012
DOI: 10.1007/s00167-012-1955-0
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the last 20 years of ACL-related in vivo-biomechanics research of the knee joint

Abstract: As a result of biomechanical research, clinicians have a better understanding of ACL injury aetiology, prevention and rehabilitation. Athletes exhibiting neuromuscular deficits predisposing them to ACL injury can be identified and enrolled into prevention programmes. Clinicians should assess ACL-reconstructed patients for excessive internal tibial rotation that may lead to poor outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 104 publications
1
37
0
2
Order By: Relevance
“…A recent cadaveric study demonstrated agreement with the proposed injury mechanism reported from ‘in vivo’ studies; increased knee valgus and anterior tibial translation (and to a lesser extent internal tibial rotation) increase ACL strain 9. Finally, biomechanical laboratory studies have contributed to the current understanding of ACL injury factors as described in a recent literature review of the past 20 years 21. In addition to the prospective coupled biomechanical-epidemiological study discussed above,10 studies have compared the biomechanics of athletes at high risk for ACL injury to those at low risk finding that female athletes, compared to males, perform athletic tasks with patterns consistent with the ligament dominance theory 22…”
Section: Introductionsupporting
confidence: 58%
“…A recent cadaveric study demonstrated agreement with the proposed injury mechanism reported from ‘in vivo’ studies; increased knee valgus and anterior tibial translation (and to a lesser extent internal tibial rotation) increase ACL strain 9. Finally, biomechanical laboratory studies have contributed to the current understanding of ACL injury factors as described in a recent literature review of the past 20 years 21. In addition to the prospective coupled biomechanical-epidemiological study discussed above,10 studies have compared the biomechanics of athletes at high risk for ACL injury to those at low risk finding that female athletes, compared to males, perform athletic tasks with patterns consistent with the ligament dominance theory 22…”
Section: Introductionsupporting
confidence: 58%
“…However, if the shear load exerted by the quadriceps is greater than the shear load exerted by the hamstrings, a resultant anteriorly directed shear force may be exerted on the proximal end of the tibia, which will potentially cause anterior tibial translation and therefore is likely to increase ACL strain [24,25]. This is known as quadriceps dominance, defined as a preferential activation of the quadriceps compared to the hamstrings when providing dynamic stability of the knee joint [26], which a number of studies have found to be greater in females than males during activities associated with ACL injury [17,[27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…An ACL injury typically occurs during the landing portion of a jump in ordinary sports activities and has a greater incidence in women than in men 1,2) . ACL deficiency may lead to degenerative changes such as tears of the meniscus.…”
Section: Introductionmentioning
confidence: 99%